Data envelopment and ridge regression analysis of paired comparison loglinear canonical model of evaluating quality circles / Zulkifley Mohamed - Mohamed, Zulkifley (Universiti Teknologi MARA Cawangan Pahang, 2000)
This paper discusses the mathematical programming approach to assess relative efficiencies within a group of Decision Making Units (DMUs) which are known as Data Envelopment Analysis (DEA) and Ridge Regression Analysis in evaluating Quality Circles (QCs).